96 Hip fracture and the influence of dementia on health outcomes and access to rehabiliation for older people. (1st September 2016) - Mitchell, Rebecca; Harvey, Lara; Brodaty, Henry; Draper, Brian; Close, Jacqui
Abstract : Background: Recovery following hip fracture can be aided by access to, and participation in, rehabilitation-related activities. However, access to rehabilitation can differ for individuals with and without dementia. This study compares the characteristics and health outcomes of individuals with and without dementia following a hip fracture; and their access to and outcomes following hospital-based rehabilitation. Methods: An examination of hip fractures involving individuals aged 65 years and older with and without dementia using linked hospital separation, rehabilitation and mortality records during 1 January 2009 to 31 December 2013 in New South Wales, Australia. Comorbidities were identified using a 1-year lookback period and a modified Charlson Comorbidity Index. Logistic regression was used to examine the association of a hospital-based rehabilitation and individual characteristics. Results: There were 8, 785 individuals with and 23, 520 individuals without dementia who sustained a hip fracture. Individuals with dementia had a higher age-adjusted 30-day mortality rate compared to individuals without dementia (11.7% vs 5.7%), a lower proportion of age-adjusted 28-day re-admission (17.3% vs 24.4%), and a longer age-adjusted mean length of stay (22.2 vs 21.9 days). Compared to individuals without dementia, individuals with dementia had 4.3 times (95% CI: 3.90–4.78) lower odds of receiving hospital-based rehabilitation. However, when they did receive rehabilitation they achieved significant motor functional gain at discharge compared to admission assessed using the Functional Independence Measure (p < 0.0001), but to a lesser extent than individuals without dementia. Conclusions: Within a population-based cohort, older individuals with dementia can benefit from access to, and participation in, rehabilitation activities following a hip fracture. This will ensure that they have the best chance of returning to their pre-fracture physical function and mobility.